As relações entre o desenho e o desenvolvimento da consciência na educação infantil à luz da Teoria Histórico-Cultural - Boriollo, Beatriz de Cássia (Universidade Federal de São Carlos, 2022)
This is a theoretical research, based on Historical-Cultural Theory, to answer the question: what is the contribution of Historical-Cultural Theory for the comprehension of the relationship between the development processes of the drawing and the child’s consciousness in the children’s education? The aim was to identify the underpinnings of the Historical-Cultural Theory necessary to relate the development of the drawing and the child’s consciousness, as well as its possible implications in the teaching practice. Therefore, through the genetic-experimental method of Historical-Cultural Theory and based on theoretical-bibliographic research, we discussed the necessity of the teachers to maximize, intentionally, the development of children’s drawings, to provide the development of higher psychological functions. As specific goals, we seek: to conceptualize the underpinnings of the drawing in the Vygotskian theory and find fundamental issues (guidelines originated from reflective abstractions) to comprehend the development process of the drawing and the child’s consciousness, and its possible implications in the pedagogical practice; to discuss the teacher’s role as enhancer of the drawing’s development. As from the immersion in the historical reality of our research subject, we identified in the drawing categories and consciousness, the analysis guidelines of data in light of Historical-Cultural Theory. In other words, the school’s role in children’s education, aesthetic and artistic education; the possibilities a teacher in children’s education of creating meaningful contexts in his/her pedagogical practices, intentionally, to the development process of the drawing and the child’s consciousness; the relationship of the higher psychological function of the drawing with the other higher psychological functions; the possibilities of the drawing also taking other roles in the child’s development and the relationships between the drawing development and the child’s consciousness development in the children’s education. The results proved our thesis: the teacher’s intentionally planned action for an aesthetic and artistic education, guided to the development process of the higher psychological functions, meaningful to a child, can promote and maximize the movement between the drawing development and the child’s awareness raising process.

La présente thèse est fondée sur la théorie historico-culturelle. Nous avons mené une recherche théorique pour répondre à la question suivante : - Quelle est la contribution de la théorie historico-culturelle à la compréhension de l'enseignant au cours du développement du dessin des enfants ? Notre objectif principal était d'identifier les fondements de la théorie historico-culturelle nécessaires au développement du dessin d'enfant dans toute sa puissance et de réfléchir aux possibles implications pédagogiques. Sur cette base, nous cherchons à encourager la réflexion des enseignants sur les possibilités de renforcer intentionnellement le développement du dessin des enfants, visant le développement des fonctions psychiques supérieures. Nous cherchons comme objectifs spécifiques: conceptualiser les fondements du dessin à partir de la théorie vygotskienne et trouver des points fondamentaux (lignes directrices issues d'abstractions réflexives) pour comprendre le processus de développement du dessin et en examiner les implications possibles dans la pratique pédagogique; discuter du rôle de l’enseignant en tant que sujet renforçant le développement du dessin. La méthodologie de recherche se fonde sur la matrice marxiste historico-dialectique, afin de, à partir de l'immersion dans la réalité historique de notre objet de recherche, identifier dans les catégories dessin et conscience les lignes directrices pour l'analyse des données à la lumière de la théorie historico-culturelle, c’est-à-dire : le rôle de l’établissement d'éducation infantile dans l’éducation esthétique et artistique ; les possibilités pour les enseignants de créer intentionnellement un nouveau contexte dans ses pratiques pédagogiques visant le processus de développement du dessin ; le rapport de la fonction psychique supérieure du dessin avec les autres fonctions psychiques supérieures ; les possibilités pour le dessin d'assumer également d'autres rôles dans le développement de l'enfant et les relations entre le développement du dessin et le développement de la conscience des enfants dans l'éducation. Les résultats ont confirmé notre thèse selon laquelle l'action pédagogique intentionnellement conçue pour une éducation esthétique et artistique, vouée au processus de développement des fonctions psychiques supérieures, ayant du sens pour l'enfant, peut favoriser le mouvement entre le développement du dessin et le processus de prise de conscience de l'enfant, tout en les renforçant.
The relationship between drawing and the development of consciousness in early childhood education in the light of Cultural-Historical Theory
La relation entre le dessin et le développement de la conscience dans l'éducation de la petite enfance à la lumière de la Théorie Historico-Culturelle
Keywords: Desenho; Consciência; Funções psíquicas superiores; Educação infantil; Educação estética; Teoria Histórico-Cultural; Drawing; Consciousness; Higher psychological functions; Children’s education; Aesthetic education; Historical-Cultural Theory; Dessin; Conscience; Fonctions psychiques supérieures; Éducation infantile; Éducation esthétique; Théorie Historico-Culturelle; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO